A novel approach to predict cetuximab‐induced hypersensitivity reaction: detection of drug‐specific IgE on basophils. (16th February 2016) - Iwamoto, Takuya; Okamoto, Akiharu; Ishinaga, Hajime; Shimizu, Kasumi; Gayle, Alberto A.; Arai, Naoya; Takeuchi, Kazuhiko; Okuda, Masahiro
Abstract: Cetuximab is remarkable for the relatively high rate and severity of hypersensitivity reactions (HR) being reported in the literature. Screening for cetuximab‐specific IgE in serum via immunoassay has been found to be useful in preventing HR; however, these tests are known to have a low positive predictive rate. In an attempt to remedy this, we evaluated the interaction between cetuximab and IgE on basophils for predicting severe cetuximab‐induced HR. Twelve head and neck cancer patients were enrolled in this single‐institution study: four with a history of cetuximab‐induced HR and eight with no such history. Cetuximab‐specific and galactose‐ α ‐1, 3‐galactose ( α ‐gal) specific IgEs in serum were measured in vitro using an enzyme‐linked immunosorbent assay (ELISA). IgE‐cetuximab binding on basophils was also analyzed to evaluate the decrease in cetuximab molecules on basophils after dissociation of IgE from FcεRI. The positive predictive value associated with the presence of cetuximab‐ or α ‐gal‐specific IgE in serum was found to be only 0.67, whereas the negative predictive value was 1.00. On the other hand, in all four patients who developed HR, the cetuximab molecules on basophils were decreased significantly due to the dissociation of IgE from basophils ( P  < 0.05). However, this was not the case in patients who did not develop HR. In conclusion, our results strongly imply that the IgE‐cetuximab interaction on basophils may be key to developing improved methods for predicting severe cetuximab‐induced HR. Abstract : We indicated for the first time that a quantification of the interaction between cetuximab and IgE on basophils, the site responsible for IgE‐mediated allergy, allows a more precise definition of the clinical presentation of allergic reaction due to cetuximab.